The Effect of Trust, Communication and Commitment on Relationship Quality and its Impact on Oyster Mushroom Supply Chain Performance in Kuningan Regency - Hamdani, Alex Busro; Yusuf, Ade; Hidayat, Yayat Rahmat (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine whether trust, communication, and commitment in relationships have an impact on supply chain performance, with relationship quality as the intervening variable. This study is a case study conducted on mushroom farmers and processors in Kuningan Regency. This study uses trust, communication, and relationship commitment as independent variables, and supply chain performance as the dependent variable, and relationship quality as an intervening variable. The method used is quantitative research with a survey approach. Data from the five variables were analyzed using the Structural Equation Model (SEM) with the help of Smart PLS (Partial Least Square) Software version 3.0. This study involved 150 respondents as samples. The results of the data analysis showed that trust, communication, and relationship commitment positively and significantly affect relationship quality, and the quality of the relationship is able to mediate the influence of the three variables on supply chain performance.